Investigation on Gas-Soot Flow Distribution Characteristic of Soot Capture Process in the Wall-Flow Diesel Particulate Filter - Jianyu Li; Chunping Lu; Dongli Tan (International Journal of Aerospace Engineering)
In order to investigate the distribution characteristics of gas-particle two-phase flow in the diesel particulate filter in the capture process, a mathematical model of gas-particle two-phase flow for inside-and-outside filter had been established in the capture process according to the mass conservation equation, momentum conservation equation, and k-ε turbulence equation. The model verification was carried out with the experimental and simulated of flow distribution characteristics of gas-particle two-phase. The obtained results showed that the static pressure gradient along the radial distribution was greater at the inlet of the filter in capture process in the diesel particulate filter, which could easily lead to causing eventual fatigue damage due to stress concentration in the front-end of filter; moreover, the weaker the vortex strength of gas-particle formed in expansion pipe was, the better uniformity of flow velocity and soot concentration distribution were. Therefore, the established mathematical model can be used for predicting gas-particle flow velocity distribution in the diesel particulate filter.